Mining of closed high utility itemsets: A survey - Singh K.; Singh S.S.; Luhach A.K.; Kumar A.; Biswas B. (My University, 2025)
Finding High Utility Itemsets (HUIs) is one of the major problems in the area of frequent itemsets mining. However, HUIs mine lots of redundant itemsets which degrade the performance and importance of high utility itemsets mining. For overcoming this limitation, closed HUIs mining has been proposed. Closed high utility itemsets mining finds complete and non-redundant itemsets. In this paper, we give recent studies on closed high utility itemsets mining algorithms. The main goal of this survey is to provide recent studies and future research opportunities. We give taxonomy of closed high utility itemsets mining algorithms. This paper provides a rough outline of the recent work and gives a general view of closed high utility itemsets mining field. © 2021 Bentham Science Publishers.